2010
DOI: 10.1378/chest.10-0187
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Spirometric Decline in New York City Firefighters With α;1-Antitrypsin Deficiency

Abstract: FDNY rescue workers with AAT deficiency had significant spirometric decline accelerations and persistent airway symptoms during the first 4 years after WTC exposure, representing a novel gene-by-environment interaction. Clinically meaningful decline acceleration occurred even with the mild serum AAT level reductions associated with PiS heterozygosity (without concomitant PiZ heterozygosity).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…Serum inflammatory biomarkers are also elevated in COPD exacerbations (49)(50)(51). We have recently reported that low a 1 -antitrypsin, elevated granulocyte-macrophage colonystimulating factor, and macrophage-derived chemokine are additional risk factors for the development of WTC-related lung injury (52)(53)(54). The contribution of the serum glucose became nonsignificant in the final model.…”
Section: Discussionmentioning
confidence: 99%
“…Serum inflammatory biomarkers are also elevated in COPD exacerbations (49)(50)(51). We have recently reported that low a 1 -antitrypsin, elevated granulocyte-macrophage colonystimulating factor, and macrophage-derived chemokine are additional risk factors for the development of WTC-related lung injury (52)(53)(54). The contribution of the serum glucose became nonsignificant in the final model.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently identifi ed moderate reductions of a 1 -antitrypsin as another risk factor for accelerated decline of lung function after WTC exposure. 26 The sensitivity of the model containing GM-CSF and MDC is low, so biomarkers defi ning other pathways to disease are likely undiscovered. Other pathways to disease need to be defi ned for serum biomarkers to be clinically useful in directing therapy designed to prevent airfl ow obstruction after irritant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The average age was 46 years and 40 years in MZ and MM individuals, respectively. After September 11, the MZ subjects exhibited a 110 mL annual decline in FEV1, compared to 25-50 mL in their MM counterparts [77]. MEHTA et al [78] also found that exposure to dust, vapour, gas and fumes was associated with a greater decline in lung function among 97 MZ when compared to 3546 MM individuals with the same level of exposure.…”
Section: Effects Of Environmental and Occupational Exposuresmentioning
confidence: 96%